EFFECT OF POSITIONING AND DIAPHRAGMATIC BREATHING EXERCISE ON RESPIRATORY RATE IN TRAUMATIC BRAIN INJURY PATIENT WITH POST-VENTILATORY SUPPORT - RABBANA R. PATEL,; JAVID H.SAGAR,; G. Varadharajulu, (International Journal of Psychosocial Rehabilitation, 2020)
This study was undertaken with the aim to determine the effect of positioning and diaphragmatic breathing exercise on respiratory rate in traumatic brain injury patient with post- ventilatory support. The basic objective of this study was to find out the effect of positioning and diaphragmatic breathingexercises protocol in traumatic brain injury patient with post-ventilatory support. This study was done in Krishna hospital, Karad. 32 patients who were diagnosed for traumatic brain injury patient with post-ventilatorysupport with age group between 25-55 years divided into two groups, 23 were males and 9 females. A thorough respiratory assessment was performed and outcome was seen with respiratory rate and oxygen saturation (Sp02).First Group A was treated with positioning and Group B was treated with diaphragmatic breathing exercise protocol for 2 weeks. The pre and post-intervention score was measured with pulse oximetry.Statistical analysis was done by using Instat software in which Wilcoxon Matched Pairs Test and Mann Whitney Test were used to analyze scores of respiratory rate and oxygen saturation(Sp02). The given treatments were significantly effective in Group B in normalizing the respiratory rate and oxygen saturation (SpO2) as compared in between Group A and Group B.Statistical analysis revealed that there was extremely significant difference between pre and post values of respiratory rate of each group (A and B) (P value= 0.0001) and extremely significant difference between post values of both the groups(A and B) (P value=